2022
DOI: 10.1039/d1ta09729f
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional CoOOH nanoframes confining high-density Mo single atoms for large-current-density oxygen evolution

Abstract: Layered transition-metal oxyhydroxides (MOOHs) emerge as promising noble-metal-free electrocatalysts for oxygen evolution reaction (OER), yet are subject to limited number of active sites at edges with inactive basal plane. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…58,59 As shown in the FI-IR spectrum of CeO 2 /Co 4 N after the OER (Figure S10), the appearance of a peak at 1154 cm −1 can further confirm the formation of CoOOH, while the peak at 1238 cm −1 could be attributed to the adsorbed OH − . 60,61 The above results have confirmed our hypothesis that the in situ generated CoOOH on the surface of Co 4 N is the active site for the alkaline OER.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…58,59 As shown in the FI-IR spectrum of CeO 2 /Co 4 N after the OER (Figure S10), the appearance of a peak at 1154 cm −1 can further confirm the formation of CoOOH, while the peak at 1238 cm −1 could be attributed to the adsorbed OH − . 60,61 The above results have confirmed our hypothesis that the in situ generated CoOOH on the surface of Co 4 N is the active site for the alkaline OER.…”
Section: Resultssupporting
confidence: 84%
“…Representative Raman peaks of CeO 2 and Co 4 N can be found at around 473 and 670 cm –1 , respectively (Figure h) . With the increase of potential, the intensity of these two peaks decreases gradually, and two new peaks appear at 509 and 584 cm –1 , which is assigned to the formation of CoOOH. , The Co 4 N on the surface is easily oxidized into CoOOH to generate CoOOH/Co 4 N, which could accelerate the conversion of absorbed hydroxy components into molecular oxygen. , As shown in the FI-IR spectrum of CeO 2 /Co 4 N after the OER (Figure S10), the appearance of a peak at 1154 cm –1 can further confirm the formation of CoOOH, while the peak at 1238 cm –1 could be attributed to the adsorbed OH – . , The above results have confirmed our hypothesis that the in situ generated CoOOH on the surface of Co 4 N is the active site for the alkaline OER.…”
Section: Resultsmentioning
confidence: 89%
“…Tang et al reported that the rich in-plane active sites can be generated by the lattice-confined Mo atoms to activate the basal plane of Mo-CoOOH with three-dimensional (3D) nanoframes, where the lattice-confined Mo sites in the two dimensional (2D) basal-plane are active sites for OER, which can bond moderately with the reaction intermediates and thereby enhance the activity. [7] He et al fabricated ultra-thin NiFe (oxy) hydroxides with Mo doping by a sacrificial template-directed approach, and further proposed that Mo doping can upshift the O 2p band in NiFe (oxy) hydroxide, weaken the metal-oxygen bond, facilitate the formation of oxygen defects, and thus change the reaction pathway to achieve excellent intrinsic OER activity. [8] 2À in NiFe nanosheets with 3D hierarchical structure to provide more active sites for hydroxide adsorption and oxidation, which also favors mass and charge transport, and draw electrons to aggrandize the valence of 3d metals in OER.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al. reported that the rich in‐plane active sites can be generated by the lattice‐confined Mo atoms to activate the basal plane of Mo‐CoOOH with three‐dimensional (3D) nanoframes, where the lattice‐confined Mo sites in the two dimensional (2D) basal‐plane are active sites for OER, which can bond moderately with the reaction intermediates and thereby enhance the activity [7] . He et al.…”
Section: Introductionmentioning
confidence: 99%
“…2 Tremendous advances have shown that rst-row 3d transition metal compounds are attractive OER electrocatalysts, especially Ni and Co oxides/hydroxides. [3][4][5] Recently, it has been reported that earth-abundant Fe and V could effectively improve the activities of these Ni and Co based catalysts. [6][7][8] In particular, the favorable local coordination and electronic structure of Fe and V made the host material a state-of-the-art OER electrocatalyst.…”
mentioning
confidence: 99%